A unique protein kinase C‐dependent pathway for tissue factor downregulation in pericytes. (1st March 2019) - Sommerville, Laura J.; Gorman, Kristen L.; Snyder, Stacey A.; Monroe, Dougald M.; Hoffman, Maureane
Abstract : Essentials Many mediators increase tissue factor (TF) expression in a wide variety of cell types. The only known example of TF downregulation is by pericytes during wound healing angiogenesis. Downregulation of TF mRNA and protein in cultured pericytes is Protein Kinase C (PKC) dependent. Pericyte TF regulation is unique, since PKC mediates increased TF in all other cell types tested. Summary: Background: Embryonic and tumor‐associated angiogenesis are linked to elevated expression of the procoagulant transmembrane receptor tissue factor (TF). In contrast, we have reported that high baseline TF expression by perivascular cells (pericytes) is dramatically reduced during angiogenesis at sites of wound healing. This is the only setting in which active TF downregulation has been reported, thus revealing a novel mechanism of TF regulation. Objectives: To define the mechanisms underlying the unique pattern of TF expression in pericytes. Methods: TF expression in primary cultures of human pericytes is not altered by angiogenic cytokines or growth factors, but is actively downregulated by phorbol 12‐myristate 13‐acetate (PMA). We characterized TF transcription, protein stability and trafficking in response to PMA. Results: Exposure to PMA reduced TF mRNA synthesis and shortened the half‐life of TF protein from 11 h to 4.5 h. Addition of PMA rapidly triggered endocytosis of cell surface TF, followed by degradation in lysosomes. Cell surface TF coagulant activity was maintained until internal stores were depleted. Reduction of TF transcription, TF endocytosis and enhanced degradation of TF protein were all blocked by broad‐spectrum inhibitors of protein kinase C (PKC). This was a surprising finding, because PKC activation increases TF expression in other cell types that have been tested. Conclusions: The unique PKC‐dependent pathway of TF downregulation in pericytes suggests that TF downregulation may play a functional role in angiogenesis. Distinct pathways regulating pathological and physiological TF expression could be utilized to modulate TF expression for therapeutic purposes.